Factor Of Non-Performing Financing (NPF) At Sharia Banking - Aliefia Indah Miftanunzein; Nana Diana (Fakultas Bisnis, 2022)
Banks have duties as institutions that provide funding and lending. Therefore, banks must pay attention to NPF factors to prevent non-performing financing and maintain bank health. The purpose of this study was to determine the factors that influence the NPF of Islamic banks in the Financial Services Authority (OJK). The research method used is quantitative with multiple linear regression testing. The data used in this study is annual data for the period 2017-2020. The variables used in this study were NPF as the dependent variable, and CAR, FDR, Inflation, SBIS, BOPO as independent variables. The results of the research that have been carried out are that CAR and BOPO have a positive and significant effect on NPF, while FDR, Inflation, and SBIS have a negative and insignificant effect on NPF.